CNTNAP3 Associated ATG16L1 Expression and Crohn's Disease - Yu Qi Qiao; Mei Lan Huang; Qing Zheng; Tian Rong Wang; An Tao Xu; Yuan Cao; Di Zhao; Zhi Hua Ran; Jun Shen (Hindawi Limited, 2015)
Autophagy is a common physiological process in cell homeostasis and regulation. Autophagy-related gene mutations and autophagy disorders are important in Crohn's disease (CD). The nucleotide oligomerization domain 2-autophagy genes autophagy 16-like 1 (NOD2-ATG16L1) signaling axis disorder contributes to the dysfunction of autophagy. This paper is focused on the relationship between contactin associated protein-like 3 (CNTNAP3) and ATG16L1 expression in Crohn's disease. The results indicated that the expression of ATG16L1 is higher in some CD patients compared to normal controls. ATG16L1 was well correlated with the C-reactive protein (CRP) in some CD patients. In vitro study revealed that CNTNAP3 could upregulate the expression of ATG16L1 and increase autophagy vacuoles.